KARBON AKTIF HASIL DEKOMPOSISI TERMAL LIMBAH KERAK CAT BESERTA KARAKTERISASINYA - Yohanes Susanto Ridwan (Research Center for Chemistry - LIPI, 2009)
Automotive sector which is one of the biggest industry has been producing paint sludge waste in enormous amount that could be dangerous for environment sustainability. To overcome this problem of course waste treatment approach is important, butsomehow the big investment and operational cost is often become restriction in adopting this kind of approach.Another alternative was to process the paint sludge waste onto more useful product (recycle). The large fraction of organic material in paint sludge has leaded an opportunity to recycle this waste ontoactivated carbon through thermal decomposition and activation process. Thermal decomposition process in 310°C without activation step has produce activated carbon which has iod number 104.81 mg/g, while the same decomposition process continue with activation step give iod number 91.87 mg/g. These results indicate that paint sludge waste could be recycle onto activated carbon which not only could reduce the environmentpollution but also could give economical benefit. Another characterization also done by DTA and FTIR to get additional information about the surface topography and chemicalfunctional groups of activated carbonproduced.Keyword: adsorben t, activation, thermaldecomposition, activated carbon, paintsludge